1994
DOI: 10.1002/cne.903490202
|View full text |Cite
|
Sign up to set email alerts
|

Projections from the lateral and interposed cerebellar nuclei to the thalamus of the rat: A light and electron microscopic study using single and double anterograde labelling

Abstract: The lateral and interposed cerebellar nuclei may have different functions in the control of movement. Efferent fibres from both nuclei project predominantly to areas of the thalamus, which in turn project to the motor cortex. In this study, single and double anterograde-tracing techniques have been used to examine and compare the pathways from the lateral and interposed nuclei to the thalamus in the rat by using both light and electron microscopy to look for evidence of organisational or structural features th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
80
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 43 publications
17
80
0
Order By: Relevance
“…It has been thought for many years that the dentate and interpositus cerebellar nuclei are involved in different aspects of motor control (Eccles, 1969;Allen and Tsukahara, 1974). Indeed, we have already demonstrated that interpositus projects to rostral VL, and dentate projects to caudal VL in the rat (Aumann et al, 1994). Given the topographical differences in the cells of origin of the different thalamocortical projections found in the present study (discussed above), it is possible that interpositus projects to cortical layer V only (via VL) and that dentate projects to layers I, III, and V. Also, neurones with different patterns of sensory receptive fields have been identified in the motor thalamus of primates (Horne and Porter, 1980), and there may be a differential distribution of receptive field types (cutaneous vs. deep) in the motor cortex of monkeys (Tanji and Wise, 1981) and cats (Pappas and Strick, 1981a).…”
Section: Cortical Laminar Distribution Of Motor Thalamic Terminalsmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been thought for many years that the dentate and interpositus cerebellar nuclei are involved in different aspects of motor control (Eccles, 1969;Allen and Tsukahara, 1974). Indeed, we have already demonstrated that interpositus projects to rostral VL, and dentate projects to caudal VL in the rat (Aumann et al, 1994). Given the topographical differences in the cells of origin of the different thalamocortical projections found in the present study (discussed above), it is possible that interpositus projects to cortical layer V only (via VL) and that dentate projects to layers I, III, and V. Also, neurones with different patterns of sensory receptive fields have been identified in the motor thalamus of primates (Horne and Porter, 1980), and there may be a differential distribution of receptive field types (cutaneous vs. deep) in the motor cortex of monkeys (Tanji and Wise, 1981) and cats (Pappas and Strick, 1981a).…”
Section: Cortical Laminar Distribution Of Motor Thalamic Terminalsmentioning
confidence: 90%
“…The brain was removed and left overnight at 4°C in fixative plus 20% sucrose. It was serially sectioned (50 µm thick) in the coronal plane on a freezing microtome, and the sections were processed histochemically according to the diaminobenzidine (DAB) protocol detailed previously (Aumann et al, 1994). The sections were mounted on gelatinized slides, air dried, stained with 1% neutral red, dehydrated, cleared, and coverslipped.…”
Section: Preparation Of Tissue For Light Microscopymentioning
confidence: 99%
“…Cerebellar projections to the ZI and/or the ventral lateral geniculate nucleus have also been shown in other species (opossum: Martin et al, 1974;Walsh and Ebner, 1993;rat: Zimny et al, 1986;rabbit;Vaudano and Legg, 1992;cat: Graybiel, 1974;Sugimoto et al, 1981) but scarcely with such an intensity or to such an extent (with regard to rat, see, e.g., Angaut et al, 1985;Aumann et al, 1994). In the dog and the monkey, subthalamic projections appear particularly sparse, if present at all (Kalil, 1981;Roullier et al, 1994;Sakai and Patton, 1993;Sakai et al, 1996).…”
Section: Subthalamic Target Areasmentioning
confidence: 89%
“…Thus, the intensity of the cerebellar projection to the VAm/VM, compared with the remaining portions of VAC, is much more prominent in the tenrec than in the rat (Deniau et al, 1992;Aumann et al, 1994). The highdensity projection to the VAm, furthermore, is not considered to be due primarily to fibers passing across this area (for a comparison of sparse VM input with previous data in rats, see Aumann et al, 1994), because 1) it is a focal projection that often is separated from the remaining target areas by a poorly labeled interspace, and 2) the areas of origin of the cerebellar projections vary with regard to the VAm and the VAcl. The prominence of the cerebellar projection to the VAm, in addition, is accentuated by the fact that this projection is bilateral, whereas the cerebellar projections to the remaining portions of the VAC are exclusively contralateral.…”
Section: Ventromedial Nuclear Complexmentioning
confidence: 93%
See 1 more Smart Citation